Kerangka pembangunan dan penilaian modul belajar cara belajar Bahasa Melayu pelajar asing Institusi Pengajian Tinggi Malaysia - Fa’izah Abd.Manan; Mohamed Amin Embi; Zamri Mahamod (Penerbit Universiti Kebangsaan Malaysia, 2010)
As a means of safeguarding the sovereignty of the education of Bahasa Melayu (BM) and to strengthen the Higher Education Institutions (HEIs), a marked change or reformation was carried out in the BM education system. BM which was once taught only to local students has now been introduced to foreign students as a compulsory subject. Various issues were brought up. Among those often discussed are that a majority of the foreign students taking BM courses in HEIs face various problems and are weak in acquiring the language skills taught to them within such a short period of time. This weakness directly affects their studies and academic achievement as a whole. Thus, this article aims to discuss the design of a framework for the development and evaluation of a module on Learning-how-to-Learn Bahasa Melayu for foreign students in Malaysian HEIs. This framework was built based on the phases in instructional design which was adapted from the ADDIE Model consisting of five major phases; analysis, design, development, implementation and evaluation. In general, the framework explains the phases which can be implemented to design and evaluate BCB BM PA Module which aims to increase the use of strategies or techniques of learning BM among foreign students in Malaysians HEIs in terms of the five skills of BM learning; listening, reading, speaking, writing and vocabulary